2021
DOI: 10.31234/osf.io/r23sa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID Feel Good – A Self-Help Virtual Therapeutic Experience for Overcoming the Psychological Distress of the COVID-19 Pandemic: Results from a European Multicentric Trial

Abstract: The primary aim of the present study was to investigate the efficacy of a self-help virtual therapeutic experience (COVID Feel Good) for reducing the psychological burden experienced during the COVID-19 lockdown across different countries. For this purpose, we focused on participants recruited from June 2020 to May 2021 in the context of a European multicenter project including four university/academic sites. Primary outcome measures were depression, anxiety and stress symptoms, perceived stress levels and hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Consistent with previous findings [34,35], we found that the COVID Feel Good intervention was effective at reducing the psychological distress experienced during the COVID-19 pandemic in a Persian population sample. Our self-help training is based on the immersive 360 • video "Secret Garden," which allows participants to explore a lovely and natural setting while being guided by a validated technique to induce relaxation and self-reflection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous findings [34,35], we found that the COVID Feel Good intervention was effective at reducing the psychological distress experienced during the COVID-19 pandemic in a Persian population sample. Our self-help training is based on the immersive 360 • video "Secret Garden," which allows participants to explore a lovely and natural setting while being guided by a validated technique to induce relaxation and self-reflection.…”
Section: Discussionsupporting
confidence: 91%
“…As part of a larger multicentric project [35], the findings of this study provided more evidence for the protocol's effectiveness across different contexts and countries. The proposed protocol has several advantages for adequately supporting individuals dealing with mental health issues related to the COVID-19 pandemic: it provides easy, self-guided training that can be accessed via a variety of digital platforms.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The overall scope of the current special issue of Psychosomatic Medicine is on “The Impact of Technological Innovation on Biobehavioral and Psychosomatic Medicine.” A comprehensive overview of technological innovations is provided with the goal that these and related innovations will be incorporated into research and clinical practice. The articles in this issue address the following general topics: the use of biological and behavioral sensors that are linked to user smartphones (8–13), the use of technology in clinical settings and issues related to VHs in clinical settings (14,15), digital mental health interventions (16,17), and the importance of reducing health disparities in technological development and implementation of technological innovation (18).…”
Section: Introductionmentioning
confidence: 99%
“…However, as with all interventions, engagement is paramount to clinical outcomes. Riva et al (16) report the efficacy of the COVID Feel Good virtual reality–based self-help intervention at reducing psychological distress and improving perceived social connections during the COVID-19 lockdowns in four European countries. These findings add to our understanding of how digital therapies can be used at-scale to relieve psychological distress during a pandemic (their intervention can be delivered via smartphone or YouTube and is currently available in 16 languages).…”
Section: Introductionmentioning
confidence: 99%